Kesenian Jurig Sarengseng Sebagai Materi Ajar Seni Budaya Kelas 8A MTsN 2 Banjar - Muhtar, Agustiana; Apriani, Arni (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
This study aims to examine the art of Jurig Sarengseng as a teaching material in learning arts and culture for class 8A students at MTsN 2 Banjar City. Jurig Sarengseng art is one of the traditional arts that developed in the Banjar City area, which contains elements of dance, music, and local cultural values. However, the existence of this art has begun to fade along with the development of the times and the lack of preservation in the context of formal education. Therefore, this study was conducted to determine the extent to which the art of Jurig Sarengseng can be preserved in the learning process and its impact on students' understanding and appreciation of local culture. The method used in this study is a qualitative descriptive method with data collection techniques in the form of observation, interviews, and documentation. The subjects of the study were class 8A students. The results of the study showed that the use of Jurig Sarengseng art as a teaching material was able to increase students' enthusiasm and active participation in learning. Students became more interested in learning regional arts because the material taught was close to their environment and daily lives.